Polyacrylonitrile / polyamide composite porous membrane as well as preparation method and application thereof

The cross-linked polyacrylonitrile/polyamide composite porous membrane was prepared by electrospinning technology, which solved the problems of insufficient mechanical properties and porosity of the electrospinning fiber membrane, and achieved the effects of high porosity, excellent structural stability and high water flux.

CN119746657APending Publication Date: 2025-04-04ZHONGYUAN ENGINEERING COLLEGE
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411950192.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The electrospinned fiber membrane has shortcomings in mechanical properties and porosity, which leads to the problems of stratification and low water flux in applications.

Method used

Using the preparation method of polyacrylonitrile/polyamide composite porous membrane, the polyacrylonitrile and polyamide spinning liquid are synchronously spinned by electrospinning technology to form a crosslinked fiber structure, and physical crosslinking between the fibers is achieved through heat treatment.

Benefits of technology

The porosity and pore connectivity of the membrane are improved, structural stability and tensile strength are enhanced, and excellent water flux is shown in the field of water treatment or separation filtration.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119746657A_ABST
    Figure CN119746657A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of organic porous membranes, and discloses a polyacrylonitrile / polyamide composite porous membrane as well as a preparation method and application thereof. The preparation method comprises the following steps: respectively dissolving polyacrylonitrile and polyamide to obtain a spinning solution, and carrying out synchronous spinning by using double-needle electrostatic spinning equipment to obtain a polyacrylonitrile / polyamide composite fiber membrane; and carrying out heat treatment to obtain the polyacrylonitrile / polyamide composite porous membrane. In the composite porous membrane, polyacrylonitrile exists in a submicron fiber structure, and polyamide is bonded on polyacrylonitrile fibers in an irregular structure. The problems that a common porous membrane is low in porosity, poor in pore connectivity and low in water flux, layers of electrostatic spinning fiber membranes are prone to layering, and the mechanical property is poor are solved; and the preparation process is simple and suitable for industrial batch production. The obtained porous membrane is stable in structure, high in porosity, good in pore connectivity and high in water flux, and has great application potential in water treatment, separation and filtration and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of organic porous membranes and relates to an electrostatic spinning porous membrane. Background Art

[0002] Porous membrane is a thin film material with a microporous structure, and its pore size is usually in the range of 0.02~10 μm. Compared with inorganic porous membranes, polymer porous membranes have the advantages of light weight, low price, and good processing performance. Polymer porous membranes can be prepared by phase inversion method, stretching method, electrospinning method, solution casting method, trace etching method, template method and other methods.

[0003] As an advanced nanofiber preparation technology, electrospinning produces electrospun fiber membranes with the advantages of small fiber diameter, high porosity, and good pore connectivity, making electrospun fiber membranes widely studied for use in textiles, catalysis, energy, and the environment. However, due to the lack of crosslinking between electrospun fibers, stratification is likely to occur between fiber layers, and the resulting fiber membranes have poor mechanical properties, which affects the application of electrospun fiber membranes in many fields. Chemical or physical methods can usually be used to achieve crosslinking between electrospun fibers to improve the problems of stratification and poor mechanical properties. The chemical method is to use chemical reagents such as glutaraldehyde and citric acid to induce chemical reactions between fibers to achieve covalent crosslinking and improve their mechanical properties. The physical method is to use solvent fumigation, hot pressing and other techniques to promote physical crosslinking between fibers through van der Waals bonds or hydrogen bonds to improve their mechanical properties.

[0004] Publication number CN 109621739 A discloses a high-throughput polyvinylidene fluoride porous membrane hydrophilic modification method, firstly prepares the polyvinylidene fluoride porous membrane by phase inversion method, then fixes tannic acid, metal ions and polyvinyl pyrrolidone to the inside of the polyvinylidene fluoride by complexation, and prepares the high-throughput polyvinylidene fluoride porous membrane. Publication number CN 115646216A discloses a hydrophilic porous membrane and its preparation method, firstly crosslinks a polyamine compound with β-cyclodextrin to obtain a crosslinked product, and then extrudes it through coating or hollow fiber spinneret to obtain a hydrophilic porous membrane with high throughput. Publication number CN117679954 A discloses a high-throughput anti-pollution polyethersulfone flat microporous membrane and its preparation method and application, firstly prepares the polyethersulfone film by solution casting method, and uses organic alcohol as curing delay agent, and uses inorganic salt as modification inducer in coagulation bath to prepare the high-throughput polyethersulfone microporous membrane. Publication No. CN 118904124 A discloses a high-throughput polytetrafluoroethylene filter membrane and a preparation method thereof. First, the polytetrafluoroethylene membrane is pretreated with an ethanol solution containing a surfactant, and then immersed in a solution of monomers, additives, deionized water and initiators for chemical reaction to obtain a high-throughput polytetrafluoroethylene filter membrane. Publication No. CN 118416713 A discloses the preparation and adsorption application of a high-throughput, fast adsorption adsorption membrane. First, MOFs (UiO-66-NH2) is prepared by hydrothermal synthesis, and then added to a mixed electrospinning solution of polyacrylonitrile and polyethyleneimine, and a spinning membrane is prepared by electrospinning.

[0005] Although the above inventions all use specific preparation methods to innovatively prepare high-flux organic membrane materials, research on how to simplify the preparation process and further improve the flux of organic porous membranes still needs to be studied. Summary of the invention

[0006] In view of the above technical problems, the present invention proposes a polyacrylonitrile / polyamide composite porous membrane and its preparation method and application. The interior of the composite membrane is made of cross-linked polyacrylonitrile fibers stacked crosswise, and has a connected pore structure, which solves the problems of low porosity, poor pore connectivity, and low water flux of ordinary polymer membranes, and solves the problems of easy delamination and poor mechanical properties of polyacrylonitrile electrospun fiber membranes.

[0007] To achieve the above object, the technical solution of the present invention is implemented as follows: A method for preparing a polyacrylonitrile / polyamide composite porous membrane, comprising the following steps: (1) Adding polyacrylonitrile polymer to solvent A, stirring for a certain period of time to allow the polyacrylonitrile to fully dissolve in the solvent, and then standing to remove bubbles to obtain a polyacrylonitrile spinning solution; (2) adding a polyamide polymer to solvent B, stirring for a certain period of time to allow the polyamide to be fully dissolved in the solvent, and then standing to remove bubbles to obtain a polyamide spinning solution; (3) Loading polyacrylonitrile spinning solution and polyamide spinning solution into syringes respectively, using a double-needle electrospinning device, adjusting the electrospinning parameters, so that the polyacrylonitrile and polyamide spinning solutions are synchronously spun onto a receiving device. Spinning for a certain period of time, a polyacrylonitrile / polyamide composite fiber membrane with a fiber structure is obtained; (4) The polyacrylonitrile / polyamide composite fiber membrane is transferred between two glass plates, the heat treatment temperature is adjusted, heat treatment is performed, and after cooling, the polyacrylonitrile / polyamide composite porous membrane is obtained.

[0008] The content of polyacrylonitrile in the polyacrylonitrile spinning solution is 8-12 wt %, The content of polyamide in the polyamide spinning solution is 2.5-5 wt%.

[0009] The solvent A is one or more of N,N-dimethylformamide, N,N-dimethylacetamide and hexafluoroisopropanol.

[0010] The above polyamide is a homopolymer or a copolymer, and its melting temperature should be lower than the melting temperature of polyacrylonitrile.

[0011] The above-mentioned polyamide is one or more of polyamide 12, polyamide 11, polyamide 6 and polyamide 66.

[0012] The solvent B is one or more of formic acid, acetic acid and hexafluoroisopropanol.

[0013] The electrospinning equipment in step (3) above should be able to simultaneously spin polyacrylonitrile and polyamide spinning solutions onto a receiving device. The injection speed is 0.1-2 mL / h, the voltage is 15-30 kV, the receiving distance is 5-30 cm, and the electrospinning time is not less than 1 h.

[0014] Furthermore, the injection speed was 0.8-1.2 mL / h, the voltage was 22-30 kV, the receiving distance was 15-20 cm, and the electrospinning time was 5-15 h.

[0015] The heat treatment temperature in the above step (4) is 170-260°C and the time is 5-30 min.

[0016] The polyacrylonitrile / polyamide composite porous membrane prepared by the above preparation method has a cross-stacked cross-linked polyacrylonitrile fiber inside, has a connected pore structure, a porosity of 61-81%, and an average pore size of 0.34-0.68 μm.

[0017] The above-mentioned polyacrylonitrile / polyamide composite porous membrane is used in the field of water treatment or separation and filtration.

[0018] The beneficial effects produced by the present invention are: (1) Compared with porous membranes prepared by other non-electrospinning technologies, the porous membrane prepared by the electrospinning technology in the present invention has the advantages of high porosity and good pore connectivity. The pure water flux under a pressure of 0.2 MPa can reach 5.9×10 4 L / (m 2 h).

[0019] (2) Compared with other non-cross-linked electrospun porous membranes, the present invention achieves adhesion between fibers through physical cross-linking. The composite membrane has excellent structural stability and higher tensile strength than the non-cross-linked electrospun fiber membrane.

[0020] (3) Compared with chemical cross-linking technology, the present invention realizes physical cross-linking between polyacrylonitrile electrospun fibers by thermal melting of polyamide electrospun fibers, does not require the use of small molecule chemical cross-linking agents, and has a simple process.

[0021] (4) Compared with other physical cross-linking technologies, the number of cross-linking points between polyacrylonitrile electrospun fibers in the present invention is large, and the cross-linking points are evenly distributed in the vertical direction, which effectively ensures sufficient adhesion between fibers and connectivity of pores. The degree of cross-linking can be controlled by the concentration and injection speed of the polyamide spinning solution.

[0022] (5) Compared with other existing technologies, the present invention only involves three steps: preparation of spinning solution, electrospinning and heat treatment. The preparation process is simple and the amount of organic solvent used in the preparation process is small, which can reduce environmental pollution and waste liquid treatment costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0024] Figure 1 1 is a SEM image of the polyacrylonitrile / polyamide composite fiber membrane obtained in Example 1, wherein (A) is a SEM image of the surface; and (B) is a SEM image of the cross section.

[0025] Figure 2 1 is a SEM image of the polyacrylonitrile / polyamide composite porous membrane obtained in Example 1; wherein (A) is a SEM image of the surface before heat treatment; and (B) is a SEM image of the cross section after heat treatment.

[0026] Figure 3 These are SEM images of the polyacrylonitrile membrane obtained in Example 1; wherein (A) is a SEM image of the surface before heat treatment; and (B) is a SEM image of the cross section after heat treatment.

[0027] Figure 4 These are SEM images of the polyamide membrane obtained in Comparative Example 2; wherein (A) is a SEM image of the surface before heat treatment; and (B) is a SEM image of the cross section after heat treatment.

[0028] Figure 5 3 is a stress-strain curve diagram of the films prepared in Examples 1-3, Comparative Example 1 and Comparative Example 2. DETAILED DESCRIPTION

[0029] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] Example 1 The preparation method of the polyacrylonitrile / polyamide composite porous membrane of this embodiment comprises the following steps: Step (1): 2.0 g polyacrylonitrile (Mw = 15×10 4 ) powder was added into 19.0 mL N,N-dimethylformamide, stirred at room temperature for 12 h to fully dissolve the polyacrylonitrile, and then allowed to stand to remove bubbles, to obtain a 10 wt% polyacrylonitrile spinning solution; Step (2): 0.7 g of polyamide 12 (PA12, Mw = 8.6 × 10 4 ) particles were added into 12.1 mL of hexafluoroisopropanol, stirred at room temperature for 10 h to fully dissolve polyamide 12, and then allowed to stand to remove bubbles, to obtain a 3.5 wt% polyamide 12 spinning solution; Step (3): 10 wt% polyacrylonitrile spinning solution and 3.5 wt% polyamide 12 spinning solution were respectively loaded into syringes, and a double-needle electrospinning device was used to simultaneously spin the polyacrylonitrile and polyamide 12 spinning solutions onto a receiving roller. The spinning voltage was set to 23.5 kV, the injection speed was 1 mL / h, the receiving distance was 17 cm, and the receiving roller speed was 500 rpm. After spinning for 13.3 h, the solution was left in the air for 12 h to allow the solvent to completely evaporate, thereby obtaining a polyacrylonitrile / polyamide 12 composite fiber membrane with a fiber structure; Step (4): Transfer the polyacrylonitrile / polyamide 12 composite fiber membrane to the middle of two glass plates, place it in a 170°C oven for heat treatment for 30 min, open the oven, allow the membrane to cool naturally and then take it out to obtain a polyacrylonitrile / polyamide 12 composite porous membrane.

[0031] The porosity of the polyacrylonitrile / polyamide 12 composite porous membrane obtained in this example is 80%, the average pore size is 0.34 μm, and the tensile strength is 5.4 MPa. In the cross-flow filtration experiment, the pure water flux at a pressure of 0.2 MPa is 5.9×10 4 L / (m 2 ·h), the pure water flux at 0.6 MPa pressure is 11.9×10 4 L / (m 2 h).

[0032] Figure 1 This is a SEM image of the polyacrylonitrile / polyamide composite fiber membrane obtained in Example 1. Figure 1 Figure (A) is a SEM image of the surface of the polyacrylonitrile / polyamide 12 composite fiber membrane obtained in Example 1. It can be seen from the figure that the polyacrylonitrile and polyamide in the composite fiber membrane are both present in a fiber structure, and the fibers are staggered, and a large number of pores are formed between the fibers. Figure 1 (B) is a SEM image of the cross section of the polyacrylonitrile / polyamide 12 composite fiber membrane obtained in Example 1. It can be seen from the figure that the fibers in the composite fiber membrane are loosely arranged in the vertical direction, and there is an obvious stratification phenomenon.

[0033] Figure 2 This is a SEM image of the polyacrylonitrile / polyamide composite porous membrane obtained in Example 1. Figure 2 Figure (A) is a SEM image of the surface of the polyacrylonitrile / polyamide 12 composite porous membrane obtained in Example 1. It can be seen from the figure that after the heat treatment, a small amount of fibers melted to form an irregular structure, and the fibers were adhered to each other. Figure 2 Figure (B) is a SEM image of the cross section of the polyacrylonitrile / polyamide 12 composite porous membrane obtained in Example 1. It can be seen from the figure that after heat treatment, the fibers in the composite fiber membrane are closely arranged in the vertical direction without delamination.

[0034] Example 2 The preparation method of the polyacrylonitrile / polyamide composite porous membrane of this embodiment comprises the following steps: Step (1): 2.0 g polyacrylonitrile (Mw = 15×10 4 ) powder was added into 19.0 mL N,N-dimethylformamide, stirred at room temperature for 12 h to fully dissolve the polyacrylonitrile, and then allowed to stand to remove bubbles, to obtain a 10 wt% polyacrylonitrile spinning solution; Step (2): 1.0 g of polyamide 12 (Mw = 8.6 × 104 ) particles were added into 11.9 mL of hexafluoroisopropanol, stirred at room temperature for 10 h to fully dissolve polyamide 12, and then allowed to stand to remove bubbles, to obtain a 5 wt% polyamide 12 spinning solution; Step (3): 10 wt% polyacrylonitrile spinning solution and 5 wt% polyamide 12 spinning solution are respectively loaded into syringes, and a double-needle electrospinning device is used to simultaneously spin the polyacrylonitrile and polyamide 12 spinning solutions onto a receiving roller. The spinning voltage is set to 23.5 kV, the injection speed is 1 mL / h, the receiving distance is 17 cm, and the receiving roller speed is 500 rpm. After spinning for 12 hours, the solution is left in the air for 12 hours to allow the solvent to completely evaporate, thereby obtaining a polyacrylonitrile / polyamide 12 composite fiber membrane with a fiber structure; Step (4): Transfer the polyacrylonitrile / polyamide 12 composite fiber membrane to the middle of two glass plates, place it in a 170°C oven for heat treatment for 30 min, open the oven, allow the membrane to cool naturally and then take it out to obtain a polyacrylonitrile / polyamide 12 composite porous membrane.

[0035] The porosity of the polyacrylonitrile / polyamide 12 composite porous membrane obtained in this example is 61%, the average pore size is 0.68 μm, and the tensile strength is 6.6 MPa. In the cross-flow filtration experiment, the pure water flux at a pressure of 0.2 MPa is 2.3×10 4 L / (m 2 ·h), the pure water flux at 0.6 MPa pressure is 7.1×10 4 L / (m 2 h).

[0036] Example 3 The preparation method of the polyacrylonitrile / polyamide composite porous membrane of this embodiment comprises the following steps: Step (1): 2.0 g polyacrylonitrile (Mw = 15×10 4 ) powder was added into 19.0 mL N,N-dimethylformamide, stirred at room temperature for 12 h to fully dissolve the polyacrylonitrile, and then allowed to stand to remove bubbles, to obtain a 10 wt% polyacrylonitrile spinning solution; Step (2): 0.5 g polyamide 12 (Mw = 8.6 × 10 4 ) particles were added into 12.2 mL of hexafluoroisopropanol, stirred at room temperature for 10 h to fully dissolve polyamide 12, and then allowed to stand to remove bubbles, to obtain a 2.5 wt% polyamide 12 spinning solution; Step (3): 10 wt% polyacrylonitrile spinning solution and 2.5 wt% polyamide 12 spinning solution were respectively loaded into syringes, and a double-needle electrospinning device was used to simultaneously spin the polyacrylonitrile and polyamide 12 spinning solutions onto a receiving roller. The spinning voltage was set to 23.5 kV, the injection speed was 1 mL / h, the receiving distance was 17 cm, and the receiving roller speed was 500 rpm. After spinning for 14.4 h, the solution was left in the air for 12 h to allow the solvent to completely evaporate, thereby obtaining a polyacrylonitrile / polyamide 12 composite fiber membrane with a fiber structure; Step (4): Transfer the polyacrylonitrile / polyamide 12 composite fiber membrane to the middle of two glass plates, place it in a 170°C oven for heat treatment for 30 min, open the oven, allow the membrane to cool naturally and then take it out to obtain a polyacrylonitrile / polyamide 12 composite porous membrane.

[0037] The porosity of the polyacrylonitrile / polyamide 12 composite porous membrane obtained in this example is 81%, the average pore size is 0.57 μm, and the tensile strength is 3.9 MPa. In the cross-flow filtration experiment, the pure water flux at a pressure of 0.2 MPa is 4.2×10 4 L / (m 2 ·h), the pure water flux at 0.6 MPa pressure is 9.2×10 4 L / (m 2 h).

[0038] Example 4 The preparation method of the polyacrylonitrile / polyamide composite porous membrane of this embodiment comprises the following steps: Step (1): 1.6 g polyacrylonitrile (Mw = 15×10 4 ) powder was added into 19.5 mL N,N-dimethylformamide, stirred at room temperature for 12 h to fully dissolve the polyacrylonitrile, and then allowed to stand to remove bubbles, to obtain 8 wt% polyacrylonitrile spinning solution; Step (2): 0.5 g polyamide 6 (Mw = 10 × 10 4 ) particles were added into 12.2 mL of hexafluoroisopropanol, stirred at room temperature for 10 h to fully dissolve the polyamide 6, and then allowed to stand to remove bubbles, to obtain a 2.5 wt% polyamide 6 spinning solution; Step (3): 8 wt% polyacrylonitrile spinning solution and 2.5 wt% polyamide 6 spinning solution are respectively loaded into syringes, and a double-needle electrospinning device is used to simultaneously spin the polyacrylonitrile and polyamide 6 spinning solutions onto a receiving roller. The spinning voltage is set to 30 kV, the injection speed is 1.2 mL / h, the receiving distance is 15 cm, and the receiving roller speed is 500 rpm. After spinning for 15 hours, the solution is left in the air for 12 hours to allow the solvent to completely evaporate, thereby obtaining a polyacrylonitrile / polyamide 6 composite fiber membrane with a fiber structure; Step (4): Transfer the polyacrylonitrile / polyamide 6 composite fiber membrane to the middle of two glass plates, place it in a 260°C oven for heat treatment for 5 min, open the oven, allow the membrane to cool naturally and then take it out to obtain a polyacrylonitrile / polyamide 6 composite porous membrane.

[0039] Example 5 The preparation method of the polyacrylonitrile / polyamide composite porous membrane of this embodiment comprises the following steps: Step (1): 2.4 g polyacrylonitrile (Mw = 15×10 4 ) powder was added into 18.6 mL N,N-dimethylacetamide, stirred at room temperature for 12 h to fully dissolve the polyacrylonitrile, and then allowed to stand to remove bubbles, to obtain a 12 wt% polyacrylonitrile spinning solution; Step (2): 0.7 g of polyamide 6 (Mw = 8.6 × 10 4 ) particles were added into 12.1 mL of hexafluoroisopropanol, stirred at room temperature for 10 h to fully dissolve the polyamide 6, and then allowed to stand to remove bubbles, to obtain a 3.5 wt% polyamide 6 spinning solution; Step (3): 12 wt% polyacrylonitrile spinning solution and 3.5 wt% polyamide 6 spinning solution are respectively loaded into syringes, and a double-needle electrospinning device is used to simultaneously spin the polyacrylonitrile and polyamide 6 spinning solutions onto a receiving roller. The spinning voltage is set to 22 kV, the injection speed is set to 0.8 mL / h, the receiving distance is set to 20 cm, and the receiving roller speed is set to 500 rpm. After spinning for 5 h, the solution is left in the air for 12 h to allow the solvent to completely evaporate, thereby obtaining a polyacrylonitrile / polyamide 6 composite fiber membrane with a fiber structure; Step (4): Transfer the polyacrylonitrile / polyamide 6 composite fiber membrane to the middle of two glass plates, place it in a 230°C oven for heat treatment for 30 min, open the oven, allow the membrane to cool naturally and then take it out to obtain a polyacrylonitrile / polyamide 6 composite porous membrane.

[0040] Example 6 The preparation method of the polyacrylonitrile / polyamide composite porous membrane of this embodiment comprises the following steps: Step (1): 2.4 g polyacrylonitrile (Mw = 15×10 4 ) powder was added into 18.6 mL N,N-dimethylacetamide, stirred at room temperature for 12 h to fully dissolve the polyacrylonitrile, and then allowed to stand to remove bubbles, to obtain a 12 wt% polyacrylonitrile spinning solution; Step (2): 0.7 g of polyamide 12 (Mw = 8.6 × 10 4 ) particles were added into 12.1 mL of hexafluoroisopropanol, stirred at room temperature for 10 h to fully dissolve polyamide 12, and then allowed to stand to remove bubbles, to obtain a 3.5 wt% polyamide 12 spinning solution; Step (3): 12 wt% polyacrylonitrile spinning solution and 3.5 wt% polyamide 12 spinning solution are respectively loaded into syringes, and a double-needle electrospinning device is used to simultaneously spin the polyacrylonitrile and polyamide 12 spinning solutions onto a receiving roller. The spinning voltage is set to 22 kV, the injection speed is set to 0.8 mL / h, the receiving distance is set to 20 cm, and the receiving roller speed is set to 500 rpm. After spinning for 12 h, the solution is allowed to stand for 12 h to allow the solvent to completely evaporate, thereby obtaining a polyacrylonitrile / polyamide 12 composite fiber membrane with a fiber structure; Step (4): Transfer the polyacrylonitrile / polyamide 12 composite fiber membrane to the middle of two glass plates, place it in a 200°C oven for heat treatment for 10 min, open the oven, allow the membrane to cool naturally and then take it out to obtain a polyacrylonitrile / polyamide 12 composite porous membrane.

[0041] Comparative Example 1 A method for preparing an electrostatically spun polyacrylonitrile membrane comprises the following steps: Step (1): 2.0 g polyacrylonitrile (Mw = 15×10 4 ) powder was added into 19.0 mL N,N-dimethylformamide, stirred at room temperature for 12 h to fully dissolve the polyacrylonitrile, and then allowed to stand to remove bubbles, to obtain a 10 wt% polyacrylonitrile spinning solution; Step (2): 10 wt% polyacrylonitrile spinning solution was loaded into two syringes, and the polyacrylonitrile spinning solution was spun onto a receiving roller using a double-needle electrospinning device. The spinning voltage was set to 23.5 kV, the injection speed was set to 1 mL / h, the receiving distance was set to 17 cm, and the receiving roller speed was set to 500 rpm. After spinning for 9 h, the solution was allowed to stand for 12 h to allow the solvent to completely evaporate, thereby obtaining a polyacrylonitrile fiber membrane with a fiber structure. Step (4): Transfer the polyacrylonitrile fiber membrane to the middle of two glass plates, place it in a 170°C oven for heat treatment for 30 minutes, open the oven, allow the membrane to cool naturally, and then take it out to obtain a polyacrylonitrile membrane.

[0042] The porosity of the polyacrylonitrile membrane obtained in this comparative example is 91%, the average pore size is 0.67 μm, and the tensile strength is 1.9 MPa. In the cross-flow filtration experiment, the pure water flux at a pressure of 0.2 MPa is 5.7×10 4 L / (m 2 ·h), the pure water flux at 0.6 MPa pressure is 11.7×10 4 L / (m 2 h).

[0043] Figure 3 : is a SEM image of the polyacrylonitrile film obtained in this comparative example. Figure 3Figure (A) is a SEM image of the surface of the obtained polyacrylonitrile membrane. It can be seen from the figure that after heat treatment, no fiber melts and there is no obvious adhesion between the fibers, which has a typical electrospun fiber membrane structure. Figure 3 Figure (B) is a SEM image of the cross section of the obtained polyacrylonitrile membrane. It can be seen from the figure that after heat treatment, the fibers in the fiber membrane are still loosely arranged in the vertical direction, and there is an obvious stratification phenomenon.

[0044] Comparative Example 2 A method for preparing electrospun polyamide comprises the following steps: Step (1): 1 g of polyamide 12 (Mw = 8.6×10 4 ) particles were added into 11.9 mL of hexafluoroisopropanol, stirred at room temperature for 10 h to fully dissolve polyamide 12, and then allowed to stand to remove bubbles, to obtain a 5 wt% polyamide 12 spinning solution; Step (2): 5 wt% polyamide 12 spinning solution was loaded into two syringes, and the polyamide 12 spinning solution was spun onto a receiving roller using a double-needle electrospinning device. The spinning voltage was set to 23.5 kV, the injection speed was set to 1 mL / h, the receiving distance was set to 17 cm, and the receiving roller speed was set to 500 rpm. After spinning for 18 h, the solution was left in the air for 12 h to allow the solvent to completely evaporate, thereby obtaining a polyamide 12 fiber membrane with a fiber structure; Step (4): Transfer the polyamide 12 fiber membrane between two glass plates, place it in a 170°C oven for heat treatment for 30 minutes, open the oven, allow the membrane to cool naturally, and then take it out to obtain a polyamide 12 membrane.

[0045] The tensile strength of the polyamide 12 membrane obtained in this comparative example is 11.4 MPa. In the cross-flow filtration experiment, the pure water flux at a pressure of 0.2 MPa is 15.1 L / (m 2 ·h), the pure water flux at 0.6 MPa pressure is 94.7 L / (m 2 h).

[0046] Figure 4 : is a SEM image of the polyamide film obtained in this comparative example. Figure 4 Figure (A) is a SEM image of the surface of the obtained polyamide 12 membrane. It can be seen from the figure that after heat treatment, the fiber structure completely disappears and a dense polymer membrane is formed. Figure 4 Figure (B) is a SEM image of the cross section of the polyamide 12 film obtained in Example 2. It can be seen from the figure that after heat treatment, the film is closely arranged in the vertical direction without delamination.

[0047] Figure 5 1 is a stress-strain curve diagram of the films prepared in Examples 1-3, Comparative Example 1 and Comparative Example 2. Figure 5Figure (A) is a stress-strain curve of the polyacrylonitrile / polyamide 12 composite porous membrane obtained in Examples 1-3 and the polyacrylonitrile membrane obtained in Comparative Example 1. It can be seen from the figure that the tensile strength of the polyacrylonitrile / polyamide 12 composite porous membrane is higher than that of the polyacrylonitrile membrane. Figure 5 Figure (B) is a stress-strain curve of the polyamide 12 film obtained in Comparative Example 2. It can be seen from the figure that its tensile strength and elongation at break are higher than those of the polyamide film.

[0048] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a polyacrylonitrile / polyamide composite porous membrane, characterized in that: Here are the steps: (1) dissolving polyacrylonitrile in solvent A to prepare polyacrylonitrile spinning solution; dissolving polyamide in solvent B to prepare polyamide spinning solution; (2) performing synchronous electrospinning of polyacrylonitrile spinning solution and polyamide spinning solution to obtain polyacrylonitrile / polyamide composite fiber membrane; wherein the process conditions of synchronous electrospinning are: injection speed of 0.1-2 mL / h, voltage of 15-30 kV, and receiving distance of 5-30 cm; (3) The polyacrylonitrile / polyamide composite fiber membrane is heat-treated to obtain a polyacrylonitrile / polyamide composite porous membrane.

2. The method for preparing the polyacrylonitrile / polyamide composite porous membrane according to claim 1, characterized in that: The content of polyacrylonitrile in the polyacrylonitrile spinning solution is 8-12 wt %, and the content of polyamide in the polyamide spinning solution is 2.5-5 wt %.

3. The method for preparing the polyacrylonitrile / polyamide composite porous membrane according to claim 1 or 2, characterized in that: The solvent A is one or more of N,N-dimethylformamide, N,N-dimethylacetamide and hexafluoroisopropanol.

4. The method for preparing the polyacrylonitrile / polyamide composite porous membrane according to claim 1 or 2, characterized in that: The solvent B is one or more of formic acid, acetic acid and hexafluoroisopropanol.

5. The method for preparing the polyacrylonitrile / polyamide composite porous membrane according to claim 4, characterized in that: The polyamide is a homopolymer or a copolymer.

6. The method for preparing the polyacrylonitrile / polyamide composite porous membrane according to claim 5, characterized in that: The polyamide is one or more of polyamide 12, polyamide 11, polyamide 6 and polyamide 66.

7. The method for preparing the polyacrylonitrile / polyamide composite porous membrane according to claim 6, characterized in that: The heat treatment temperature is 170-260°C and the time is 5-30 min.

8. A polyacrylonitrile / polyamide composite porous membrane prepared by the preparation method according to any one of claims 1 or 2 or 5 to 8.

9. The polyacrylonitrile / polyamide composite porous membrane according to claim 8, characterized in that: The porosity of the polyacrylonitrile / polyamide composite porous membrane is 61-81%, and the average pore size is 0.34-0.68 μm.

10. Use of the polyacrylonitrile / polyamide composite porous membrane according to claim 9 in the field of water treatment or separation and filtration.

Citation Information

Patent Citations

  • Hydrophilic modification method of high-flux PVDF porous membrane

    CN109621739A

  • Hydrophilic porous membrane and preparation method thereof

    CN115646216A

  • High-flux anti-pollution polyether sulfone flat microporous membrane as well as preparation method and application thereof

    CN117679954A

  • Preparation and adsorption application of high-flux and fast-adsorption adsorption film

    CN118416713A

  • High-flux polytetrafluoroethylene filter membrane and preparation method thereof

    CN118904124A